Thermal performance of parabolic concentrators under Malaysian conditions - Rafeeu, Yaaseen (2011)
Renewable energy generation is becoming more prevalent on today’s electric grid. The challenges of increasing the percentage of renewable energy will be dealing with the intermittent nature of renewable sources. This thesis outlines various existing solar technologies. The understanding of each technology and its associated challenges provide a suitable basis to recognize advantages and drawbacks, more importantly it gives the technological development of solar dish concentrator. Three experimental models with various geometrical sizes and diameter of about 0.5m of solar dish concentrators are used to analyze the effect of geometry on a solar irradiation and temperature and in maximising the solar fraction under Malaysian environment. These models are used to analyze the performance of parabolic concentrating collector’s parameters such as reflector materials, aperture diameter, depth of concentrator, size of focal point and temperature at the focal point with different solar irradiations to increase the thermal efficiency. There are 3 dishes involved which described as D1, D2 and D3. D1 is having depth of 5cm, focal point of 26.45cm and D2 is having depth of 15cm, focal point 10.42cm. The reflective material of these 2 dishes are 3M aluminium films while D3 having shiny stainless steel as a reflector with depth of 10cm and focal point of 12.66cm. The absorbers were fabricated from 85cm length of copper tube of 4 mm in diameter spiralled and positioned at the focal point. Components of the concentrated solar power technology such as reflectors and turbine/engines are quite mature in the market development. However, there is opportunity for improvements where new techniques can be adopted. Solar concentrator systems are among the alternatives that can be used to develop an improved and efficient renewable energy system. The enormous solar potentials in Malaysia could be used to bringing significant social and economic benefits in both rural and urban areas. At present there are many factors that would limit the implementation of renewable energy systems in Malaysia, particularly solar dish concentrators. Thermal efficiency of the different dimensional dish concentrators are analysed using an absorber placed at the focal point. There is a significant variation in the efficiency of the concentrator with different reflective materials used. The efficiencies are calculated and results are conclusive. The 3M Silverlux aluminium films are much efficient than shiny stainless steel and increasing the area of the concentrator gives much more considerable variation in the results i.e. efficiency when comparing with the base. Overall, the efficiency of D1 and D2 is over 60% compared to D3, which is 50% in many cases (by neglecting the losses). Finally, the results conclude that concentrator D3 is less efficient compared with other two concentrators. Although the results in this thesis could be used to develop efficient solar dish concentrators in Malaysia, there is still more research need to be done in improving current technology of dish concentrator systems, as the higher the efficiency of solar dish concentrators, the greater the role of renewable energy in the near future.